Sense Differentiation In Electronic And Print Dictionaries: A Comparative Study Of Dictionary Efficacy - Tan, Kim Hua (2007)
This study compared the efficacy of the electronic dictionary with that of the print dictionary in helping learners differentiate senses of polysemous words in dictionaries.